2020
DOI: 10.1186/s13071-020-04320-x
|View full text |Cite
|
Sign up to set email alerts
|

Teladorsagia circumcincta beta tubulin: the presence of the E198L polymorphism on its own is associated with benzimidazole resistance

Abstract: Background Benzimidazole resistance is associated with isotype-1 β-tubulin gene F200Y, E198A and F167Y SNPs. In this study, the recently described polymorphism E198L was reported and analysed in Teladorsagia circumcincta. Methods The benzimidazole phenotypic resistance was measured by the faecal egg count reduction test (FECRT) and the egg hatch test (EHT) using a discriminating dose (DD) in 39 sheep flocks. Around 1000 larvae collected before and after treatment were used for DNA extraction. The resistant s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…Initially, the amino acid exchanges F200Y [ 21 , 22 ], F167Y [ 23 , 24 ] and sometimes E198A [ 25 ] were predominantly reported in many resistant parasite populations. Recently, additional exchanges in codons 198, in particular E198L and E198V in resistant strongyle nematodes, have raised attention at least in some geographical regions [ 26 , 27 , 28 , 29 , 30 , 31 ]. Based on the knowledge that these mutations can confer resistance to BZs, epidemiological surveys have been established to rapidly identify BZ-resistant parasite populations, using methods such as pyrosequencing [ 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], droplet digital PCR [ 31 , 40 ] or deep amplicon sequencing [ 29 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the amino acid exchanges F200Y [ 21 , 22 ], F167Y [ 23 , 24 ] and sometimes E198A [ 25 ] were predominantly reported in many resistant parasite populations. Recently, additional exchanges in codons 198, in particular E198L and E198V in resistant strongyle nematodes, have raised attention at least in some geographical regions [ 26 , 27 , 28 , 29 , 30 , 31 ]. Based on the knowledge that these mutations can confer resistance to BZs, epidemiological surveys have been established to rapidly identify BZ-resistant parasite populations, using methods such as pyrosequencing [ 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], droplet digital PCR [ 31 , 40 ] or deep amplicon sequencing [ 29 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study from Spain, the frequency of E198L (GAA/CTA) was found to be highly associated with the response to BZ treatment in sheep naturally infected with T. circumcincta . In this study, the frequency of leucine was changed from the range of 10.4–80.7% in samples before treatment to a range of 82.3–92.8% after treatment [ 53 ]. In a very important new publication, leucine, alanine and valine were introduced at codon position 198 of the ben-1 β-tubulin isotype into the BZ susceptible, free-living Bristol N2 Caenorhabditis elegans using CRISPR/Cas-9 mediated genome editing followed by exposure to different concentrations of albendazole and fenbendazole.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP F200Y has been shown to be strongly associated with low efficacy of benzimidazoles, whereas the SNPs F167Y and E198A have been occasionally related with anthelmintic resistance [ 28 ]. Besides that, the presence of the E198L polymorphism on its own, a substitution of glutamate to leucine, was very recently related to benzimidazole resistance in H. contortus and T. circumcincta , two gastrointestinal nematodes infecting ruminants [ 19 , 29 ]. In humans, only SNP F200Y has been associated with low efficacy of benzimidazoles in T. trichiura in one study [ 10 ], since the authors observed an increment in the resistant genotype in individual eggs collected after treatment.…”
Section: Discussionmentioning
confidence: 99%